Survey of ICT and Education in Africa : Ethiopia Country Report - World Bank (Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Leapfrogging is the word most technical people would use to describe the advancement, at least in infrastructure, that has occurred in Ethiopia in less than 10 years. Even though the country may still have one of the lowest tele-densities in the continent, there are signs that this situation will soon change. The WoredaNet, the e-government communication backbone, developed by the Ethiopian Telecommunication Corporation, is a promise and a major enabler for rapid ICT development in the country. Already the public sector and the education sector have begun to benefit from this network, and the health and agriculture sectors have been lined up for the next phase. With all this and a corresponding ICT for education policy and implementation plan, Ethiopia is set to become a model ICT user on the continent. The infrastructure seems to be falling into place and the policies and strategies are already there. The challenge now is for the government to effectively co-ordinate the implementation of the strategy.